Analisis Desain Pasif pada Bangunan Masjid di Banda Aceh terhadap Pendinginan, Pencahayaan, dan Kebisingan - Quratul Aini; Effendi Nurzal; Cut Putri Nahrisyah (Universitas Sebelas Maret Surakarta, 2025)
Cooling, lighting, and noise are crucial aspects that must be considered for building comfort, significantly influenced by the performance of design elements. As a primary solution before resorting to mechanical systems, passive design elements, such as windows, ventilation, building form, and orientation should be utilized optimally. However, some mosques indicate a decline in the use of these elements, particularly in cooling and natural lighting. This study analyzed the effectiveness of passive design in mosques in Banda Aceh. The case study of 10 mosque buildings reveals that passive design elements fail to meet cooling needs, leading to a high dependence on mechanical systems such as air conditioning (AC). The natural lighting (daylighting) functions effectively due to the implementation of side lighting and top lighting systems, while noise management is also optimal through strategies such as managing the source, using barriers, and proper zoning. The study concluded that passive design optimization in mosques needs to be carried out, especially in terms of cooling.